Single-Pollen Genotyping - Isagi, Yuji.; Suyama, Yoshihisa; SpringerLink (Online service) (Tokyo : Springer Japan, 2011)
Pollination is one of the most important processes in plant reproduction. It directly influences reproductive success and fitness and the genetic structure of the plant population. Methods exist to infer the pattern and distance of pollen dispersal, but direct observation of the movements of individual pollen grains during pollination is not feasible owing to their small size. Single-pollen genotyping is a novel technique for genotyping a single pollen grain. In this book, the principles, the experimental protocol, and several applications of this method in studies of plant ecology, reproductive biology, and evolutionary genetics have been described. More specifically, the information is useful for the analysis of linkage disequilibrium, intraspecific genetic variation, chromosome mapping, and the origins of polyploidy. It is also essential for achieving sustainable and optimal crop yield and is vital to agriculture and forestry. Written by pioneer researchers, the book provides novel research approaches that are proving useful in a growing number of fields. This volume is intended to encourage new and continued applications of single-pollen genotyping among many disciplines in the future.
1 Signifi cance of Single-Pollen Genotyping in Ecological Research -- 2 Procedure for Single-Pollen Genotyping -- 3 Pollination Effi ciencies of Insects Visiting Magnolia obovata, as Determined by Single-Pollen Genotyping -- 4 Difference in Pollen Donor Composition During the Early Phases of Reproduction as Revealed by DNA Analysis of Pollen Grains and Seeds in the Monoecious Tree Castanea crenata -- 5 Expanded Home Range of Pollinator Birds Facilitates Greater Pollen Flow of Camellia japonica in a Forest Heavily Damaged by Volcanic Activity -- 6 Can Tiny Thrips Provide Suffi cient Pollination Service During a General Flowering Period in Tropical Rainforest?- 7 Alien Dandelions Displace a Native Related Species Through Interspecifi c Pollen Transfer -- 8 Single-Pollen Genotyping of Holocene Lake Sediments -- 9 Potential Application of Pollen Genotyping for Evolutionary Genetic and Genomic Studies: Linkage/Recombination Analysis and Haplotype Sequencing -- Index.
Keywords: Life sciences; Plant Ecology; Evolution (Biology).; Botany; Life Sciences; Plant Ecology; Plant Sciences; Evolutionary Biology